Host inflammatory response is the major marker of severe respiratory syncytial virus infection in older adults. Issue 6 (December 2021) - Lui, G; Wong, CK; Chan, M; Chong, KC; Wong, R; Chu, I; Zhang, M; Li, T; Hui, DSC; Lee, N; Chan, PKS
Highlights: RSV causes severe disease in older adults. Host inflammatory response is the major marker of severe disease. There was no association between viral kinetics and disease severity. Summary: Objectives: We aim to study the viral kinetics and host inflammatory response of RSV infection in older adults, and their correlation with disease severity. Methods: We performed a prospective observational study in adults with RSV infection. We serially collected nasal-throat swabs for quantification of RSV-A and RSV-B viral load, and peripheral blood samples for measurement of cytokine/chemokine concentrations. The study endpoints were (i) requiring supplemental oxygen therapy, and (ii) non-invasive ventilation, intensive care, or died within 30 days of admission. We performed multivariable logistic regression models to identify independent variables for severe disease. Results: We enrolled 71 hospitalized patients and 10 outpatients treated for RSV infection (median age 75 years, 51% male, and 74% with comorbidities). Among hospitalized patients, 61% required supplemental oxygen therapy, and 18% had severe disease requiring non-invasive ventilation or intensive care, or died within 30 days. Inflammatory cytokine/chemokines IL-6, CXCL8/IL-8, CXCL9/MIG and CXCL10/IP-10 increased significantly during the acute phase of illness. IL-6 concentration was independently associated with severe disease after adjusting for confounding factors. RSV viral load was not associated with disease severity throughout the course of illness. Conclusion: Host inflammatory response is a major marker of severe disease in older adults with RSV infection.